Î²-MnO2 ACTIVATION OF PEROXYMONOSULFATE FOR CATALYTIC PHENOL DEGRADATION IN AQUEOUS SOLUTIONS - Saputra, Edy; Muhammad, Syaifullah; Sun, Hongqi; Ang, Ha-Ming; TadÃƒÂ©, Moses O.; Wang, Shaobin (CHEMICA: Jurnal Teknik Kimia, 2014)
Î²-MnO2 was prepared and used to activate peroxymonosulphate for degradation of aqueous phenol. The sample was characterized by N2 adsorption, X-ray diffraction (XRD), scanning electron microscopy (SEM). The catalyst is highly effective in heterogeneous activation of PMS to produce sulfate radicals for phenol degradation compared with homogeneous oxidatiom. Î²-MnO2 could completely remove phenol in 30 min at the conditions of 25 ppm phenol, 0.4 g/L catalyst, 2 g/L PMS, and 25 oC. A pseudo first order model would fit to phenol degradation kinetics and activation energy was obtained as 38.2 kJ/mol.